STUDY ON THE FAST MISSILE CRAFT OF 60 M ON THE SEASTATE CONDITION OF THE WEST AND EASTERN INDONESIAN WATER - soegeng hardjono (BRIN, 2017)
Recently, Indonesian Navy is developing warship fleet by constructing Fast Missile Craft (KCR) 60M. The performance of KCR 60MÂ depends on the wave height of Indonesian waters. It needs to perform research on the maximum wave height for the ship length of KCR 60M and the minimum ship length of KCR 60M to cope with the highest extrem waves by statistical methods and empirical formula. The analysis result shows that KCR 60M can operate at a maximum wave height of 4,73m. Since the wave height of Indonesian water is less than 4,73m, then KCR 60M can operate throughout the year, except in Desember and January in the North areas of Indonesia near the South China Sea border due to the moonsun Asia. However, the existency of the extrem wave height >4,3m cause KCR 60M unable to operate whether in the North or South Equators as well as Inter-island waters. KCR 60M also unable to operate in the whole Naval Main Base (Lantamal) from Lantamal II (Padang) up to Lantamal XIV (Sorong). Based on the average extreme wave height of 5,1m, it can be determined that KCR 60M capable of operating has a minimum ship length of about 70m.